2000
DOI: 10.2527/2000.78102639x
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between dietary lysine, sex, and porcine somatotropin administration on growth performance and protein deposition in pigs between 80 and 120 kg live weight.

Abstract: Sixty male and 60 female crossbred pigs were allocated to an experiment to investigate the effects of porcine somatotropin (pST) administration (0 or 6 mg/d) and dietary lysine content on growth performance, tissue deposition, and carcass characteristics over the live weight range of 80 to 120 kg. Pigs receiving pST were given diets containing 6.9, 7.8, 8.8, 9.7, 10.6, or 11.5 g lysine/kg, whereas control pigs received diets containing 4.8, 5.8, 6.9, 7.8, 8.8 or 9.7 g lysine/kg. These dietary levels ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 22 publications
2
27
0
4
Order By: Relevance
“…However, studies from the early 2000s suggested that, although the daily protein deposition and growth potential of entire males was greater than that of gilts, there was little difference in the lysine (g/kg feed) requirement of grower and finisher entire males and gilts O'Connell et al, 2005 and. King et al (2000) found that there was no difference in the lysine requirement to maximize protein deposition and minimize FCR in heavy (80 to 120 kg BW) finisher entire males and gilts. O'Connell et al (2005) found that, in three studies in grower entire males and gilts (20 to 68 kg BW), there were no differences in the lysine requirements (g/kg) to maximize growth and minimize FCR.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, studies from the early 2000s suggested that, although the daily protein deposition and growth potential of entire males was greater than that of gilts, there was little difference in the lysine (g/kg feed) requirement of grower and finisher entire males and gilts O'Connell et al, 2005 and. King et al (2000) found that there was no difference in the lysine requirement to maximize protein deposition and minimize FCR in heavy (80 to 120 kg BW) finisher entire males and gilts. O'Connell et al (2005) found that, in three studies in grower entire males and gilts (20 to 68 kg BW), there were no differences in the lysine requirements (g/kg) to maximize growth and minimize FCR.…”
Section: Resultsmentioning
confidence: 97%
“…per MJ digestible energy (DE)). The studies used in these analyses included those reported by Batterham et al (1985), Giles et al (1986and 1987, Hansen and Lewis (1993), King et al (2000), O'Connell et al (2005 and, Moore et al (2012) and Rikard-Bell et al (2012) with some publications containing more than one study. The meta-analysis indicated that entire males have a higher dietary lysine requirement than gilts (0.600 v. 0.549 g SID lysine/MJ DE, P 5 0.009) over the finisher stage.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments studying the dose-response relationships in pigs fed diets providing a broad range of amino acid intake showed that the group response diminished as the limiting amino acid intake approached requirement (Gahl et al, 1994;King et al, 2000). Whether the response of individuals is rectilinear or curvilinear is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with pGH also enhanced protein deposition in well-nourished growing pigs (Vann et al, 2000) and increased lysine requirements, which is commensurate with increased protein deposition in boars (King et al, 2000). Sows treated with growth hor-mone at some time during, or even late in, gestation showed an increase in progeny size at birth (Rehfeldt et al, 2004).…”
Section: Introductionmentioning
confidence: 94%